High Prevalence of Uncontrolled Hypertension Among Afghan Hypertensive Patients: A Multicenter Cross-Sectional Study - Baray AH; Stanikzai MH; Wafa MH; Akbari K (Dove Medical Press, 2023)
Ahmad Haroon Baray,1 Muhammad Haroon Stanikzai,1 Mohammad Hashim Wafa,2 Khalid Akbari3 1Department of Public Health, Faculty of Medicine, Kandahar University, Kandahar, Afghanistan; 2Neuropsychiatric and Behavioral Science Department, Faculty of Medicine, Kandahar University, Kandahar, Afghanistan; 3Internal Medicine Department, Faculty of Medicine, Paktia University, Paktia, AfghanistanCorrespondence: Muhammad Haroon Stanikzai, Department of Public Health, Faculty of Medicine, Kandahar University, District # 10, Kandahar, Afghanistan, Tel +93704775578, Email haroonstanikzai1@gmail.comBackground: Despite striking advances in the management of hypertension, blood pressure (BP) control remains suboptimal worldwide. Sustainable Development Goals (SDGs) call for 80% control rates by 2030, highlighting the urgency for improvements in hypertension control.Objective: We aimed to determine the prevalence of uncontrolled hypertension (≥ 140/90 mmHg) and assess its associated factors in Afghan hypertensive patients.Methods: We conducted this multicenter cross-sectional study at three Afghan public hospitals in Afghanistan. We recruited hypertensive patients (n=950) on antihypertensive medications (AHMs) from August to December 2022. We analyzed only complete datasets (853). We employed the 14-item Hill-Bone compliance scale to assess compliance with AHMs. We performed multivariable logistic regression analyses to determine factors associated with uncontrolled hypertension.Results: The mean age (±SD) of the patients was 47.5 (± 9.5) years and males constituted 50.5% (431) of the study sample. The prevalence of uncontrolled hypertension in this study was 77.3% (95% CI: 74.2- 79.9%). Factors associated with uncontrolled hypertension and their adjusted OR (95% CI) were physical inactivity: 3.45 (1.87- 6.35), current smoking: 3.04 (1.50- 6.15), high salt intake: 3.57 (1.9- 6.7), presence of comorbid medical disease: 2.22 (1.20- 4.08), higher BMI: 3.32 (1.12- 9.88), poor compliance to AHMs: 8.50 (4.62- 15.6), and presence of depressive symptoms: 1.99 (1.2- 3.27).Conclusion: The prevalence of uncontrolled hypertension was high in the present study. Factors associated with uncontrolled hypertension may epitomize potential targets for public/individual health interventions in Afghanistan.Keywords: hypertension, uncontrolled, prevalence, risk factors, Afghanistan